PENGARUH PENYALURAN KREDIT, TINGKAT SUKU BUNGA DAN KECUKUPAN MODAL TERHADAP PROFITABILITAS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2014 - Jurisman Simanjorang (Fakultas Ekonomi Prodi Akuntansi, 2020)
The main purpose of a company is to make profit. In calculating the benefits made by a banking company, it can use profitability ratios by using a measurement scale; that is, Return on Assets (ROA). Some of the ratios that affect the profitability of a bank include the Loan to Deposit Ratio, Interest Rates and Capital Adequecy Ratio. The research used the theories of financial accounting and banks and other financial institutions with regard to bank earnings and bank capital. The study used a quantitative approach, this type of research is descriptive, and the nature of research is explanotary. Data collection was performed by means of documentation, while data analysis was performed by multiple linear regression analysis. The populations of the study are all banks listed on the Indonesia Stock Exchange (BEI) in the period from 2012 to 2014 totaling 27 companies. The 81 samples of the study were drawn by using purposive technique. The results of this study showed that the value of Adjusted R Square was 15.6% and loan portfolio, interest rates and capital adequacy simultaneously have a significant positive effect on profitability with a significant value of 0.001. And partially, credit does not have any effect on profitability, as well as the interest rate has a significant negative effect on the profitability with the significant value of 0.01 and a capital adequacy has a significant effect on profitability with significant value of 0.01.